“Golden rice bowl of racial discrimination” : racialization of black Africans in Chinese online discussion - Puomisto, Heidi (My University, 2024)
This thesis sets out to examine race in China through tracing the details of how black Africans were discussed in April 2020 during the COVID-19 pandemic, when reports of confirmed cases of COVID-19 originating from abroad began to outnumber domestic cases which followed news reports of black Africans in the Southern Chinese city of Guangzhou facing targeted, indiscriminate pandemic measures as racialized black people. Informed by critical race approaches, this study conceptualizes race as a socially constructed tool of domination which is reproduced in discourse. The online representations of black Africans are then analyzed through primary research using the method of qualitative thematic analysis to uncover race-related themes in online discussion on the China-based social media and question-and-answer platform Zhihu (知乎). A thematically diverse, yet consistently othering portrayal of black Africans in Chinese online discussion is found. Netizens represent black Africans as social deviants, essentially different to Chinese people based on legal status/mobility patterns, behavior, and attitudes, as well as politicized subjects who, in Chinese netizens’ imaginaries, serve as conduits for broader political themes, both domestically within the PRC and in the international arena. Chinese netizens furthermore engaged in meta-discourse on racism, in which it is overwhelmingly argued that black Africans do not face discrimination in China. In line with earlier literature on the topic, the themes suggest a paradoxical view of black Africans as simultaneously inferior and superior.
Keywords: race, racialization, racism, racial discrimination, anti-blackness, social media, China